2004
DOI: 10.1016/j.chroma.2004.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of botulinum toxins type C, D, E, and F by matrix-assisted laser desorption ionisation and electrospray mass spectrometry

Abstract: In a follow-up of the earlier characterisation of botulinum toxins type A and B (BTxA and BTxB) by mass spectrometry (MS), types C, D, E, and F (BTxC, BTxD, BTxE, BTxF) were now investigated. Botulinum toxins are extremely neurotoxic bacterial toxins, likely to be used as biological warfare agent. Biologically active BTxC, BTxD, BTxE, and BTxF are comprised of a protein complex of the respective neurotoxins with non-toxic non-haemagglutinin (NTNH) and, sometimes, specific haemagglutinins (HA). These protein co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 41 publications
(54 reference statements)
1
32
0
Order By: Relevance
“…In our study, we analyzed complete progenitor toxins from serotypes A through G. Five of the strains we used in this study differed from those analyzed by van Baar et al (29,30), who used strains 62A, Okra, 003-9, CB-16, no designation (equivalent to NCTC 11219 by analysis), and Langeland from serotypes A through F, respectively (30). Okra and Langeland strains from serotypes B and F, respectively, overlapped those used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, we analyzed complete progenitor toxins from serotypes A through G. Five of the strains we used in this study differed from those analyzed by van Baar et al (29,30), who used strains 62A, Okra, 003-9, CB-16, no designation (equivalent to NCTC 11219 by analysis), and Langeland from serotypes A through F, respectively (30). Okra and Langeland strains from serotypes B and F, respectively, overlapped those used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Their MALDI-MS and LC-ESI-MS analyses of botulinum serotypes A through F identified neurotoxin and each protein present in their toxin samples. They also showed that ESI-MS with CID (ESI-MS/MS) or MALDI-MS with postsource decay identified protein unambiguously (29,30). Several neurotoxin samples they purchased included some known progenitor proteins, but they did not always include each progenitor toxin protein in each sample.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations